Deformable Boundary Initialization For Object Detection In Natural Images Using, Multiple Scale Edges. - Foon, Dah Way; Rajeswari, Mandava; Ramachandram, Dhanesh (2006)

(untitled)
The deformable contour model is a popular technique to segment object in image processing. Its applications range from edge and curve detection, to shape modeling and visual tracking.